2014
DOI: 10.1007/s00128-014-1210-0
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Cadmium and Zinc in Selected Species of Epigeic Mosses

Abstract: The sorption abilities of seven moss species growing on the area of Bory Stobrawskie forest (southern Poland) were tested in laboratory. Sorption was carried out in solutions of Zn and Cd chlorides. It has been shown that the sorption properties depend on the moss species and increases in the series as follows: Polytrichum commune < Leucobryum glaucum < Eurhynchium praelongum < Thuidium tamtariscifolium ≤ Dicranum scoparium ≤ Pleurozium schreberi < Sphagnum sp. With help of microscope images, it was also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The results presented in Figure 3 show that, for most of the analyzed elements, the relative metal accumulation occurs after 2-3 months, and is higher in mosses dried at room temperature: the conditions under which the mosses were before the exposure affect the level of the analyte accumulation. It has been shown that mosses as bioindicators (dried and still alive (Figure 2) of atmospheric aerosol contamination with heavy metals may accumulate analytes into their cells [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The results presented in Figure 3 show that, for most of the analyzed elements, the relative metal accumulation occurs after 2-3 months, and is higher in mosses dried at room temperature: the conditions under which the mosses were before the exposure affect the level of the analyte accumulation. It has been shown that mosses as bioindicators (dried and still alive (Figure 2) of atmospheric aerosol contamination with heavy metals may accumulate analytes into their cells [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of metal concentrations between P. schreberi and P. commune with the t test ( P < 0.05) revealed that P. commune contained significantly higher Cd, Cr, Ni, Pb and Zn concentrations. Busuoic et al ( 2012 ) and Kłos et al ( 2014 ) evaluated the highest values of the sorption properties of some metals for P. commune in comparison with other moss species. However, Rumyantsev et al ( 2014 ) argue that P. schreberi has the highest ability for the accumulation of especially Cu in comparison with P. commune .…”
Section: Discussionmentioning
confidence: 99%
“…Moss species adsorb and incorporate atmospheric HM deposition (Gonzales and Pokrovsky 2014) over several years but are in general rather resistant to toxic elements such as HM (Basile et al 2013;Berg and Steinnes 1997). Therefore, soil inhabiting ectohydric moss and moss bags complement technical measurements of HM deposition on different spatial scales (Aboal et al 2010;Ares et al 2012;Blagnyté and Paliulis 2010;Basile et al 2008;Boquete et al 2011Boquete et al , 2014Burton 1990;Dragović and Mihailović 2009;Giordano et al 2013;Harmens et al 2013;Kłos et al 2014;Tyler 1990;Varela et al 2013). In Europe, moss surveys help validating modeled deposition, especially with regard to the spatial resolution of deposition maps (Schröder et al 2011(Schröder et al , 2012.…”
Section: Introductionmentioning
confidence: 94%